ANTIBODIES AGAINST PARAINFLUENZA 3 VIRUS IN PIGS FROM TECHNIFIED AND BACKYARD FARMS SLAUGHTERED IN LIMA, PERU - Montesinos P., Milagros (2013)
Antibodies against Parainfluenza 3 (PI3) virus were determined in pigs from commercial (n= 192) and backyard farms (n=192). Blood samples were collected at the slaughter house from pigs of 2 to 6 months of age of any sex for detecting antibodies against the PI3 virus by viral neutralization test. The 5.5 ± 2.3% (21/384) of the pigs had antibodies against PI3 virus, where 5.2 ± 1.1% (10/192) and 5.7 ± 1.2% (11/192) were from commercial and backyard farms respectively. The antibody titres ranged from 4 to 64 and were detected in pigs older than 3 months of age. The results shows the presence of PI3 in the pig population.